Analysis of spectrally resolved thermoluminescence of LiF:Mg,Cu,P detectors by the surface fitting method using algorithm for unrestricted peak positions - Mandowska, Ewa; Mandowski, Arkadiusz; Bilski, Paweł; Świątek, Józef (Radiation protection dosimetry, 2006)
Recently developed surface fitting technique is a natural replacement for the widely used glow curve deconvolution (GCD) technique. Surface fitting can be applied for advanced spectrally resolved thermoluminescence (TL) measurements. It combines both kinetic and emission-band analysis. Owing to greater number of parameters and data points the algorithm is more time-consuming than usual GCD. However, it offers greater reliability in determination of trap parameters. This is especially important for spectrally resolved measurements that are usually performed at low-light level conditions. This paper demonstrates an application of the surface fitting method to the analysis of TL-3D data from LiF:Mg,Cu,P detectors. The spectra were analysed using two different variants of surface fitting—for restricted and unrestricted peak positions.